Metoda kolejnych przybliżeń wyznaczania kształtu belek sprężonych na podstawie hipotezy A. Caquot - Jaworski, J.; Marks, W. (Engineering Transactions, 1968)
This is a description of an efficient method for determining the form of the cross-section of a prestressed beams from the equality condition of maximum reduced stress due by n states of load. It consists in determining by iteration the thickness of flanges and webs at any number of points. The paper includes an example of determination of the form of the cross-section of a three-span railway bridge. Numerical computation has been carried out by means of the Elliott 803-B computer.